Designing and operation of pilot scale continuous stirred tank reactor for continuous production of bio‐methane from toxic waste. Issue 1 (4th May 2018) - Singhal, Shailey; Agarwal, Shilpi; Singhal, Naveen; Sharma, Rajan; Sharma, Rohit
Abstract : Increased use of biofuels from non‐renewable resources is required for sustainable development of the society. Biogas being almost pure methane, occupies importance to be used in place of compressed natural gas as transportation fuel in future. Lignocellulosic biomass (agricultural and forestry residues) are inexpensive and abundantly available source of energy. Pilot scale continuous stirred tank reactor was designed for jatropha de‐oiled cake (JDOC) with a total capacity of 40 m 3 . JDOC was digested with cow dung (3:1) in pilot scale reactor for continuous production of biogas for 120 days at 35°C. Around 20 m 3 biogas was produced per day as a regular operation in only 5 days. © 2018 American Institute of Chemical Engineers Environ Prog, 38: 198–200, 2019